Analisis Cemaran Mikroba pada Kue Loyang Dogan yang Dijual di Pasaran dan Dampaknya terhadap Keamanan Pangan - Nanik Apriyanti; Ardi Mustakim (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2025)
Loyang Dogan cake is a traditional Indonesian food commonly sold in markets without the use of modern preservation methods, making it susceptible to microbial contamination. This food is often produced and sold in conditions that may affect its quality and safety. Therefore, this study aims to provide a scientific overview of the potential microbial contamination in Loyang Dogan cakes and its benefits as an educational foundation for both producers and consumers regarding the importance of food hygiene. The focus of this research is to identify bacterial colony growth in Loyang Dogan cakes through microbiological culture tests. The method used in this study involves inoculation, starting with the dilution of the sample using sterile solutions, followed by inoculation onto a Nutrient Agar (NA) medium that has been solidified. The samples are then incubated at 37°C for 24 to 48 hours. After the incubation period, the growing colonies are observed and the number and morphological characteristics are recorded. The results show bacterial colony growth in all tested samples, with differences in the number and shape of the colonies depending on the sample source. The bacterial colonies generally appear white, cream, or yellowish, round, smooth, and vary in size. These findings indicate that Loyang Dogan cakes have the potential to be contaminated with microbes during the production and sale process, posing risks to the quality and safety of consumption. Based on the results, it is concluded that improvements in sanitation and food handling practices for traditional products like Loyang Dogan are necessary to ensure their safety for public consumption. Therefore, educating producers and consumers about food hygiene is crucial to raising awareness of the importance of maintaining food quality and safety.